“I would never have become an interpreter without social media”: online social media’s motivational dynamics in self-regulated interpreting learning - Cai, Zhiyu; Yang, Shanshan (Frontiers in Psychology, 2025)
IntroductionIn the Web 2.0 era, self-regulated learning (SRL) through online social media (OSM) has become integral to language learning, particularly for Chinese interpreting learners preparing for postgraduate programs. Despite its growing role, the impact of OSM on interpreting learners’ motivation and SRL outcomes remains underexplored.MethodsGrounded in Zimmerman’s Cyclical Model of SRL, this study employed semi-structured interviews with 29 Chinese interpreting learners to examine OSM-mediated motivational dynamics throughout the Self-regulated interpreting learning process.ResultsOur findings reveal that OSM acts as a double-edged sword. OSM significantly enhances learners’ motivation, operating both as an end-state and an ongoing process, by providing accessible resources, offering emotional support, creating platforms for community engagement, increasing interpreter visibility, and offering learning affordances that translate initial motivations into actions. Meanwhile, OSM also acts as a deterrent to and regulator of motivation due to its entertaining and social nature, which can introduce distractions, misinformation, and increased anxiety among interpreting learners, potentially hindering the effective regulation of motivation.DiscussionOur findings suggest that navigating OSM effectively requires the development of critical thinking skills. This research contributes to the understanding of OSM-mediated interpreting education and offers insights into how educators can help learners harness the benefits of OSM while mitigating its drawbacks.